ANALYSIS EFFECT OF WALL DIMENSIONS ON THERMAL RESISTANCE IN FURNACE INDUCTION 1200 â°C - Ahmad Zohari; Eka Bima Saputra; Rivaldo Rivaldo; Sigit Ariyanto; Andriansyah Andriansyah (Department of Mechanical Engineering Education, 2023)
The development of metal hardening industry using electrical induction to increase the hardening temperature chamber is very quick. The temperature can reach 1200 °C in short time by adjusting the electricity input to heater. However, the temperature can also decrease significantly, if the thermal resistance of room cannot prevent heat transfer to outside. The research method uses analysis of other research and direct measurements on induction furnace machine. The machine specifications have maximum room temperature (T1= 1200 â„ƒ), surrounding temperature (T2= 25.8 °C), and the firebrick thermal conductivity (k= 4.78 J/s m°C). Researchers focused on testing variations dimensions (breadth and thickness) of walls. Based on calculation results, the best thermal resistance is 1.1308 in dimension 2 with breadth of 259 cm2 and thickness of 14 cm. This is in accordance with theory of thermal resistance that the higher thermal resistance produced, the higher ability of material to inhibit rate of heat flow.